Gender gap in Swiss vocational education and training teachers' economics content knowledge and the role of teaching experience. (December 2019) - Holtsch, Doreen; Brückner, Sebastian; Förster, Manuel; Zlatkin-Troitschanskaia, Olga
In the commercial sector, which is of crucial importance to the Swiss economy among other countries, a large number of apprentices are trained on a vocational education and training programme every year. Besides other subjects, the subject Economics and Society forms an integral part of the vocational education and training curriculum and serves to prepare apprentices for professional, economic and civic participation. Although content knowledge is widely considered necessary to both teaching quality and student achievement, little is known about the subject-specific content knowledge of Swiss Economics and Society teachers. As previous research has shown a gender gap in the content knowledge of (pre-service) teachers in economics, we focus on the question as to whether Swiss Economics and Society teachers' economics content knowledge differs, including in relation to gender. As additional influencing factors, our study included teaching experience and teaching load. We measured the economics content knowledge of 153 Economics and Society teachers with a shortened German version of the Test of Understanding College Economics in the German-speaking part of Switzerland. Multivariate analyses indicated a gender effect that manifested itself in higher test scores among male Economics and Society teachers. These findings are relevant to the training of vocational education and training teachers.